The effect of Bacillus spp. and vermicompost on the growth of cherry tomato, Solanum lycopersicum L., fruits - Barahona-Pico, Yenny Astrid; Ortíz-Paz, Rocío Alexandra; Narváez-Ortiz, Ildefonso (Revista de Ciencias Agrícolas, 2024)
In this investigation, we evaluate the effect of Bacillus spp. and vermicompost on the growth of cherry tomato, Solanum lycopersicum L., fruits. We used four treatments: 1. Vermicompost (112 g). 2. Vermicompost (112 g) in combination with the consortium of bacteria of the genus Bacillus (B. subtilis, B. thuringiensis var. kurstaki, B. pumilus, and B. amyloliquefaciens) at a concentration of 1x108 colony forming units (CFU)/mL and in a dosasge of 3 mL/L of water. 3. The consortium of bacteria of the genus Bacillus at the concentration and dose mentioned and, 4. Control (untreated soil). Our experimental design was in the completely randomized design with three replications. We used the tomato fruit's weight, horizontal diameter, and vertical diameter as variable responses. Significant differences between treatments were assessed with one-way analysis of variance (ANOVA) and classified with Tukey's honestly significant difference (HSD) test. The assumptions of normality, homogeneity of variations, and data independence were verified. The Wilcoxon test was used to assess differences in the chemical composition of the fruits of each treatment. The results showed that the highest values of average fruit weight, 15.21 g and 12.99 g, were statistically equivalent obtained with T2 and T3; correspondingly compared to 11.86 g obtained in the control. There were no statistical differences between treatments in the vertical and horizontal diameter. It is concluded that the application of vermicompost in combination with the Bacillus consortium (T2); or individually (T3), significantly increases fruit weight and improves the nutritional value (N, P, K, Ca, S, Mg, Fe, Mn, Cu, Zn, B, and Na).